Desain Basis Data Non Relasional Nosql Mongodb pada Website Sistem Informasi Akademik - Mohamad Farozi, Mohamad Farozi (Universitas Lembah Dempo, 2019)
Non relational data bases differ from the relational database model that has been used so far. The NoSQL database is very useful in continuously developing data, where the data is so complex that a relational database can no longer accommodate. The Academic System aims to support the implementation of education, so that universities can provide better and more effective information services to their environment, both inside and outside the university through the internet. Various needs in the field of education as well as regulations that surround it are so high that the management of academic data is a work that is very time-consuming, energy and mind. MongoDB does not have tables, columns, and rows. In MongoDB there are only collections and documents. Documents contained in mongoDB can have different attributes than other documents even though they are in one collection.